Immediate Esthetic Rehabilitation of Periodontally Compromised Anterior Tooth Using Natural Tooth as Pontic. (19th April 2016) - Kumar, K. Pavan; Nujella, Surya Kumari; Gopal, S. Sujatha; Roy, K. Karthik
Abstract : For patients who require removal of anterior teeth and their replacement various treatment modalities are available. With advancement in technology and availability of glass/polyethylene fibres, use of natural tooth as pontic with fibre reinforced composite restorations offers the promising results. The present case report describes management of periodontally compromised mandibular anterior tooth using natural tooth pontic with fibre reinforcement. A 1-year follow-up showed that the bridge was intact with good esthetics and no problem was reported.